Gender measurement invariance of the learning burnout scale of undergraduates (LBSU) among Chinese undergraduates - Wei, Zhixia; Che Hassan, Norlizah; Hassan, Siti Aishah; Ismail, Normala; Gu, Xiaoxia; Dong, Jingyi (Human Resource Management Academic Research Society, 2024)
This study aimed to examine the measurement invariance of the Learning Burnout Scale of Undergraduates (LBSU) across gender, addressing a significant gap in the literature despite the scale’s widespread use in research. A sample of 619 undergraduate students was assessed using the LBSU. Both single-group and multi-group confirmatory factor analyses (CFAs) were conducted using AMOS 24.0 to evaluate the scale’s psychometric properties and gender-based measurement invariance. Findings demonstrated that the LBSU exhibits robust psychometric properties for assessing academic burnout severity among undergraduate students. Moreover, the scale demonstrated measurement invariance across genders, suggesting that observed differences between male and female participants likely reflect genuine gender disparities rather than measurement artefacts, which contributes to the methodological rigor of academic burnout research in the Chinese context. The complex pattern of gender differences observed, coupled with the moderate levels of burnout across the sample, addresses the urgency of tailored effective interventions.